A Study on How "Options" Work in Investment - A Guide to the Investors - Premkumar, N. B.; Esther Gnanapoo, J. (Indian Journal of Finance, 2008)
Nowadays, many investors' portfolios include investments such as mutual funds, stocks and bonds. But the variety of securities you have at your disposal does not end there. Another type of security, called an option, presents a world of opportunity to sophisticated investors. The power of options lies in their versatility. They enable you to adapt or adjust your position according to any situation that arises. Options can be as speculative or as conservative as you want. This means you can do everything from protecting a position from a decline to outright betting on the movement of a market or index.